Macromolecular Crowding Induces a Binding Competent Transient Structure in Intrinsically Disordered Gab1. Issue 5 (15th March 2022) - Gruber, Tobias; Lewitzky, Marc; Machner, Lisa; Weininger, Ulrich; Feller, Stephan M.; Balbach, Jochen
Graphical abstract: Highlights: NMR characterization of transient structures and dynamics of a nonphosphorylated and tyrosine phosphorylated IDP. Macromolecular crowding with biological crowders induces changes in the dynamics of the SHP2 binding regions in Gab1613–694 . The tyrosine -phosphorylated Gab1613–694 binds with nanomolar affinity to the SHP2 tandem SH2 motif. Macromolecular crowding results in transient binding of nonphoshorylated Gab1613–694 to the SHP2 tandem SH2 domains. Abstract: Intrinsically disordered proteins (IDPs) are an important class of proteins which lack tertiary structure elements. Their dynamic properties can depend on reversible post-translational modifications and the complex cellular milieu, which provides a crowded environment. Both influences the thermodynamic stability and folding of globular proteins as well as the conformational plasticity of IDPs. Here we investigate the intrinsically disordered C-terminal region (amino acids 613–694) of human Grb2-associated binding protein 1 (Gab1), which binds to the disease-relevant Src homolog region 2 (SH2) domain-containing protein tyrosine phosphatase SHP2 (PTPN11). This binding is mediated by phosphorylation at Tyr 627 and Tyr 659 in Gab1. We characterize induced structure in Gab1613–694 and binding to SHP2 by NMR, CD and ITC under non-crowding and crowding conditions, employing chemical and biological crowding agents and compare the results of the non-phosphorylated and tyrosine phosphorylated C-terminal Gab1 fragment. Our results show that under crowding conditions pre-structured motifs in two distinct regions of Gab1 are formed whereas phosphorylation has no impact on the dynamics and IDP character. These structured regions are identical to the binding regions towards SHP2. Therefore, biological crowders could induce some SHP2 binding capacity. Our results therefore indicate that high concentrations of macromolecules stabilize the preformed or excited binding state in the C-terminal Gab1 region and foster the binding to the SH2 tandem motif of SHP2, even in the absence of tyrosine phosphorylation.